Dialog II für blockflöte und computer - Schweizer, Frank, 1962- (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1989)
"Dialog II" is a composition about the songs of the humpback whales. Wales are able to compose songs, consisting of six themes, which can be each separated in 4 or 6 motives. These motives change during the travel of the whole group of whales from the North Pole to the South Pole and back wards. Time after time new motives come into the song, others are lost. This idea is the idea of the composition. Between the musician and the computer begins an interactive process, both are getting more and more to a unit. The playing of the musician controls the out put of the computer. The output of the computer controls the out put of the musician. The score exists in form of a computer score, which is put on the computer screen. The computer score is generated live while the performance and is in every performance different. The composition is a real time composition in which the musician controls with his play his intensity the process and duration of the composition.